The Fund's Income Position for FY 2012 : Midyear Review. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
This paper updates the outlook for the Fund's income position for FY 2012. The overall outlook is broadly unchanged, with the FY 2012 net operational income now projected at SDR 500 million compared with the projection of SDR 482 million in April 2011. This primarily reflects additional lending activity, which is partially offset by lower implicit returns on the Fund's interest-free resources owing to the prevailing interest rate environment.1 The actual outcome is subject to considerable uncertainty in light of conditions in the global economy, which could affect the timing and amounts of disbursements under current and potential new arrangements and the performance of the Investment Account (IA).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Financial Year; Income Position; Income; Interest Rate; PP